2019
DOI: 10.5937/straman1904021s
|View full text |Cite
|
Sign up to set email alerts
|

Strategic personnel management: Context of retirement age reform in Russia

Abstract: Since January 2019, retirement age in the Russian Federation will be gradually raised. Over the next ten years, the retirement age will be raised by five years to 60 years for women and 65 years for men. The Russian labor market is characterized by a fairly high level of ageism, manifested in the reluctance of employers to hire people older than 40-45 years, to train and promote workers of pre-retirement age. The decrease in the number of young generations and the increase in the proportion of older people act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 11 publications
0
3
0
2
Order By: Relevance
“…Human capital and their skills are the main drivers of economic growth and national competitiveness in the modern economy (Kordić & Milićević, 2018;Radivojević, Kahrović & Krstić 2019), "they introduce changes and innovations, they create additional value and they increase business efficiency, and thus the initiation of future organization performance" (Perić, Gašić, Stojiljković & Nešić, 2018, p. 618). Also, in the era of automation and digitalization, it is important to develop human capital in a firm to make them capable to handle new challenges (Nica, 2018;Stuken & Korzhova, 2019). The working arrangements have been changed a lot (Popescu, 2018) and new knowledge, skills, and abilities are needed, in terms of problem solving, critical thinking, creativity, people management, coordinating with others, emotional intelligence, STRATEGIC MANAGEMENT, Vol.25 (2020), No.…”
Section: Introductionmentioning
confidence: 99%
“…Human capital and their skills are the main drivers of economic growth and national competitiveness in the modern economy (Kordić & Milićević, 2018;Radivojević, Kahrović & Krstić 2019), "they introduce changes and innovations, they create additional value and they increase business efficiency, and thus the initiation of future organization performance" (Perić, Gašić, Stojiljković & Nešić, 2018, p. 618). Also, in the era of automation and digitalization, it is important to develop human capital in a firm to make them capable to handle new challenges (Nica, 2018;Stuken & Korzhova, 2019). The working arrangements have been changed a lot (Popescu, 2018) and new knowledge, skills, and abilities are needed, in terms of problem solving, critical thinking, creativity, people management, coordinating with others, emotional intelligence, STRATEGIC MANAGEMENT, Vol.25 (2020), No.…”
Section: Introductionmentioning
confidence: 99%
“…Based on the works of L. Gratton and E. Scott, the authors recommend moving from a three-stage life, consisting of education, career and retirement, to a multi-stage path, forming a communicative and analytical axiology. The authors' conclusions are confirmed in the forecasts of the Pew Research Center (Lloyd, 2018) and in the studies of Russian scientists (Stuken and Korzhova, 2019), who say that the most valuable skills in the future will be those that machines cannot easily reproduce, for example, creativity, critical thinking, emotional intelligence, adaptability and collaboration.…”
Section: Figure 1 Business Digitalization Index In Europe and Russiamentioning
confidence: 66%
“…De modo geral, os estudos obtidos no levantamento junto à WOS sobre práticas gerenciais e ageismo podem ser divididos em duas linhas de pesquisa: 1) identificação de atitudes e práticas ageistas no contexto organizacional (Mcvittie et al, 2003;Lu et al, 2011;Rego et al, 2018;Hanashiro & Pereira, 2020;Bartkowiak et al, 2021;Axelrad et al, 2021); 2) políticas e práticas de inserção e permanência de trabalhadores mais velhos nas organizações (Goldberg et al, 2013;Karpinska et al, 2013;Vasconcelos, 2015;Taylor & Earl, 2016;Cortijo et al, 2019;Stuken & Korzhova, 2019). O estudo de Amorim et al (2019) transita entre os dois grupos.…”
Section: Resultados E Discussõesunclassified
“…Esse cenário reforça a dificuldade de contratação e permanência do trabalhador mais velho no ambiente organizacional, que pode ser potencializada pelas características do mercado de trabalho, como alta competição e restrição de mão de obra. Apesar de haver pesquisas que apontem uma abertura à contratação de trabalhadores maduros (Goldberg et al, 2013;Stuken & Korzhova, 2019;Bartkowiak et al, 2021), ainda há poucas evidências que isso seja uma mudança generalizada. Por fim, a integração dos resultados também aponta a ausência de políticas e práticas organizacionais destinadas à força de trabalho mais velha e reforça a importância de fomentar a empregabilidade desse público.…”
Section: Considerações Finaisunclassified